2010
DOI: 10.1111/j.1365-2249.2010.04278.x
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box P3+ T cells express interleukin-17 in nasal mucosa of patients with both allergic rhinitis and polyposis

Abstract: SummaryThe pathogenesis of nasal polyposis remains unclear; it severely affects patients' quality of life and complicates inflammation in adjacent organs such as sinusitis and asthma. Aberrant immune regulatory function in these patients is proposed. The present study aims to examine the regulatory T cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Treg activation in peripheral blood cells is reported to be reduced in CRS patients compared with control patients, but most studies do not find reduced levels of the suppressive cytokines IL-10 or TGF-β (136139). Studies in noneosinophilic patients in Asian countries have shown increased presence of IL-17–producing FOXP3 + Tregs (134, 140, 141). On balance, CRS cannot be attributed to defects in Treg responses at present.…”
Section: Innate and Adaptive Inflammatory Responses Underlying The Pamentioning
confidence: 99%
“…Treg activation in peripheral blood cells is reported to be reduced in CRS patients compared with control patients, but most studies do not find reduced levels of the suppressive cytokines IL-10 or TGF-β (136139). Studies in noneosinophilic patients in Asian countries have shown increased presence of IL-17–producing FOXP3 + Tregs (134, 140, 141). On balance, CRS cannot be attributed to defects in Treg responses at present.…”
Section: Innate and Adaptive Inflammatory Responses Underlying The Pamentioning
confidence: 99%
“…Serum IL-17A levels were higher in the patients with SAR [8,9] and T H 17 cells responded to allergen [10]. IL-17A and T H 2 cytokines enhanced T H 2-driven pathology, which led to more severe disease in a murine model.…”
Section: Introductionmentioning
confidence: 95%
“…Plasma IL-17 levels were higher in the patients with AR and TH17 cells responded to allergen [12][13][14]. However, IL-17 response to SLIT in AR caused by house dust mite remains unclear.…”
Section: Changes In the Clinical Characteristics During 3 Yearsmentioning
confidence: 85%